Aspectos metodológicos da utilização do Data Mining no âmbito da Geografia - Bação, Fernando Lucas (2022)
Bação, F. L., & Painho, M. (2003). Aspectos metodológicos da utilização do Data Mining no âmbito da Geografia. Finisterra, 38(75), 135-147. https://doi.org/10.18055/Finis1584